Pengaruh Penanganan Keluhan Bagasi pada Unit Lost and Found Terhadap Kepuasan Penumpang Citilink di Bandar Udara Juanda Surabaya - Giovani Baptista Mangu Kwaelag; Desiana Rachmawati (Pusat Riset dan Inovasi Nasional, 2025)
Air transportation plays a crucial role in supporting national mobility and connectivity, especially following the recovery of the aviation industry. However, the increase in passenger numbers is often accompanied by challenges in airport services, particularly baggage handling, which becomes a source of passenger dissatisfaction. Ineffective baggage complaint handling can significantly impact the overall passenger experience. Therefore, this study aims to determine whether baggage complaint handling by the Lost and Found Unit affects the satisfaction of Citilink passengers at Juanda Airport and to measure the extent of this influence. This research uses a quantitative research method with a descriptive and causal design. The quantitative approach focuses on collecting and analyzing numerical data to test hypotheses and explain the phenomena under study. The data collection technique used is a questionnaire, designed to measure the effect of baggage complaint handling on passenger satisfaction. The population in this study includes all Citilink airline passengers who used the Lost and Found services at Juanda Airport, Surabaya, with a total population of 180,000 passengers during the period from August to September 2024. The sample was determined using the Slovin formula, resulting in 100 respondents. The research findings indicate that the Baggage Complaint Handling variable (X) has a significance level of α < 0.05 on the Passenger Satisfaction variable (Y), leading to the rejection of H0 and acceptance of Ha. Testing conducted using SPSS software yielded a partial test (t) value of 0.000 < 0.05, indicating that Baggage Complaint Handling significantly affects Passenger Satisfaction. Through simple linear regression analysis, it was found that the influence of Baggage Complaint Handling on Passenger Satisfaction is demonstrated by an Adjusted R² Square value of 0.841 or 84.1%, while the remaining 15.9% is influenced by other factors not included in this research model.